The effect of ammonia on development in Dictyostelium discoideum - Davies, L; Davies, Lynne (1994)
﻿ Upon starvation, individual amoebae of D. discoideum cooperate to produce a cell aggregate. The aggregate then elongates into a slug which moves chemotactically towards food sources. Culmination of the developmental cycle results in the formation of a fruiting body containing differentiated stalk and spore cells. Ammonia is produced naturally in the aggregates during starvation and is implicated in the regulation of the developmental cycle. Addition of excess ammonia leads to inhibition of aggregation, increased slug migration, delay of culmination and the promotion of spore formation. This thesis examines the possible intracellular mechanism(s) through which ammonia might affect developmental processes. It has been postulated that ammonia might act by directly inhibiting a particular enzymatic activity, alternatively it could act as a weak base to raise the pH of the cytosol or an intracellular compartment. To investigate these possibilities, the effects of a variety of weak bases were tested on aggregation and culmination. All of the weak bases tested inhibited development in a dose-dependent way, which argues against the notion that ammonia acts by direct enzyme inhibition since the bases are structurally distinct. In addition, the inhibition potencies of the bases varied according to their protonophoric activity: the most effective protonophores were also the most effective developmental inhibitors. This suggested that the bases were likely to be acting to neutralize an intracellular compartment in these experiments,a result which implicates acidic compartments in the control of development. That weak bases can indeed dissipate the pH of intracellular vesicles was confirmed in vitro by monitoring acidification of isolated vesicles in the presence of the bases. In vivo experiments using 31P-NMR probes of the vesicular system confirmed this and showed that cytosolic pH was stable in the presence of bases. Genetic evidence for the role of acidic compartments in development was also gathered. Both the acidification-defective (Hgr) mutants and a mutant created by antisense expression of a fraction of the B subunit cDNA of the vacuolar H+- ATPase were defective in development, displaying developmental behaviour reminiscent of weak base-treated wild-type strains. This shows that defective vacuolar acidification can mimic the effect of addition of ammonia and indicates that an acidic vesicle is the target of ammonia In vivo.